The impact of the Russian-Ukraine war on the stock market: a causal analysis - Derindere Köseoğlu, Sinem; Adıgüzel Mercangöz, Burcu; Khan, Khalid S.; Sarwar, Suleman (Routledge, 2024)
The study assumes the causal effects of the Russian-Ukraine war on the Moscow Exchange index based on forecasting the counterfactual market response. The findings suggest that the Ukraine war has a detrimental impact on the index; the effects are especially more pronounced at the beginning of the war. The results indicate a rapid divergence from counterfactual predictions and the actual stock index was consistently lower than would have been expected in the absence of war. The two curves suggest a reconvening pattern in the stock market when the stock market resumes its activities. The estimate of the Moscow Exchange index decline following the conflict and reaching the bottom is shown in the point-wise causal effect. The cumulative causal effect adds up to the causal effect in the course of time. In relative terms, the response variable decreased by ?51%. This means that the negative impact observed during the intervention period is statistically significant. The diverse economic sectors should have access to market information and pay close attention to the effects of the conflict on the stock market. Investment decisions and policy adjustments should be based on the evolution and changes in the conflict. © 2023 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: causal inference; conflict; counterfactual predicting; Stock market; Ukraine war